MENGUNGKAP BANGUNAN BERSEJARAH UNTUK MEMBANGKITKAN WISATA SEJARAH DAN BUDAYA DI SEMARANG - Romadi Romadi (JURNAL LITBANG PROVINSI JAWA TENGAH, 2006)
Many historic buildings in Semarang are precious assets of Indonesia. Mostly those buildings are inherited from Dutch Colonialism era. They were government and private buildings, and even the buildings.which were belonged by personal at that time. Due to the history of this nation, those buildings mean a lot. They are so precious for Indonesia Old City Area can reveal the very first sight ofSemarang city when Dutch built it.This area had very neat infrastructure and it was organized very well. There is a famous old building called Gereja Blenduk. Itwas builts in Portuguese colonialism, then it was completed by Dute. Another buildings which are out of Old City Area are Lawang Sewu, De Vredestein, Du Pavilion Hotel and Elisabeth Hospital. This research is aimed to rememorize and to motivate Semarang citizen to love their city more. In that way, they will give their contribution, for example, they participate themselves in the renovation of these historic buildings or to develop them. And at last these buildings can be as goals for tourism destination. To gain the purpose of the research, researcher gathered data whether written or spoken from library research and interview. He also made a cross check by doing serial interviews. After that, he selected the data, the verified them according to the scientific historical writing standard. It was done to get data which meet validity aspect.